IMPROVING THE SKILLS OF WRITING ARGUMENTATION ARTICLES FOR STUDENTS OF SMA NEGERI 5 MAKASSAR THROUGH THE SEND A PROBLEM TECHNIQUE - Rahmawati Rahmawati; Muliadi Muliadi; Sitti Rabiah (Citra Dharma Cindekia, 2022)
This study aims to determine whether there is an effect of the Send A Problem technique on the ability to write an argumentative essay. Techniques in data collection in the form of test techniques in the form of descriptions, observations and interviews. The data obtained in this study were analyzed descriptively quantitatively and qualitatively. Student learning outcomes in learning to write using the Send A Problem technique, then calculated using the formula for the average value. This is evident in the results of research that the ability to write argumentative essays has increased gradually. Cycle 1 the average value of students is 64 with a KKM value of 72, including the low category, then it is continued in cycle 2 with the results of the average score of students above the KKM which is 84. So it can be concluded that there is a significant increase from the application of the Send A Problem technique to argumentative essay writing skills of class X SMA Negeri 5 Makassar so that it is stated to have been successful and quite effectively applied in the learning process in the classroom.